How I Attend—Not How Well Do I Attend: Rethinking Developmental Frameworks of Attention and Cognition in Autism Spectrum Disorder and Typical Development. Issue 4 (7th August 2016) - Burack, Jacob A.; Russo, Natalie; Kovshoff, Hannah; Palma Fernandes, Tania; Ringo, Jason; Landry, Oriane; Iarocci, Grace
Abstract : Evidence from the study of attention among persons with autism spectrum disorder (ASD) and typically developing (TD) children suggests a rethinking of the notion that performance inherently reflects disability, ability, or capacity in favor of a more nuanced story that involves an emphasis on styles and biases that reflect real-world attending. We provide examples from behavioral and physiological research in which performance on attention tasks is not solely a function of abilities, or disabilities, per se but rather is also a function of the ways in which they are implemented. Thus, the study of attention both among persons with ASD and in typical development might best be recast in terms of the question of "how" rather than "how well."